2018
DOI: 10.1111/jace.15887
|View full text |Cite
|
Sign up to set email alerts
|

Controlled synthesis of Bi2O3/BiOBr/Zn2GeO4 heterojunction photocatalysts with enhanced photocatalytic activity

Abstract: BiOBr/Zn2GeO4 heterojunctions decorated by Bi2O3 quantum dots (QDs; named as Bi2O3/BiOBr/Zn2GeO4 hereafter) with intriguing micro/nanostructures have been constructed via a two‐step hydrothermal route. The compositions, phases, and morphologies of Bi2O3/BiOBr/Zn2GeO4 were investigated in detail. The light absorption ability, photocurrent responses, and photocatalytic degradation of methylene blue (MB) experiments were performed to evaluate the photocatalytic activity of the micro/nanoheterostructured Bi2O3/BiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…For pure Zn 2 GeO 4 component, the flower-like Zn 2 GeO 4 -DETA nanosheets exhibit the highest photocatalytic performance under UV-visible light irradiation ( Figure 8A,B), which might be ascribed to its highest specific surface area, which play a significant role in elevating photocatalytic performance. 46 For g-C 3 N 4 / Zn 2 GeO 4 composites, as results were shown in Figure 8 and Figure S2, the rod-like g-C 3 N 4 /Zn 2 GeO 4 (1:1)-EG composite with more exposed (110) facets of Zn 2 GeO 4 ( Figure 4G) exhibited the most enhanced photocatalytic performance compared to pure g-C 3 N 4 . It is reported that F I G U R E 7 UV-vis absorption spectra of (A) pure Zn 2 GeO 4 samples prepared from different solvents (Inset: plots of (αhv) 2 versus energy (hv) for the band gap energies of different Zn 2 GeO 4 ; (B) The UV-vis absorption spectra of g-C 3 N 4 and g-C 3 N 4 /Zn 2 GeO 4 (1:1) composites; (C) The UV-vis absorption spectra of g-C 3 N 4 /Zn 2 GeO 4 (0.5:1)-EG, g-C 3 N 4 /Zn 2 GeO 4 (1:1)-EG and g-C 3 N 4 /Zn 2 GeO 4 (2:1)-EG in compassion to g-C 3 the density of oxygen vacancies over the (110) surface is higher than that of the (001) surface, which are very important for the production of active •OH species as the H 2 O molecules dissociate in the oxygen vacancy.…”
Section: Photocatalytic Degradationmentioning
confidence: 69%
See 2 more Smart Citations
“…For pure Zn 2 GeO 4 component, the flower-like Zn 2 GeO 4 -DETA nanosheets exhibit the highest photocatalytic performance under UV-visible light irradiation ( Figure 8A,B), which might be ascribed to its highest specific surface area, which play a significant role in elevating photocatalytic performance. 46 For g-C 3 N 4 / Zn 2 GeO 4 composites, as results were shown in Figure 8 and Figure S2, the rod-like g-C 3 N 4 /Zn 2 GeO 4 (1:1)-EG composite with more exposed (110) facets of Zn 2 GeO 4 ( Figure 4G) exhibited the most enhanced photocatalytic performance compared to pure g-C 3 N 4 . It is reported that F I G U R E 7 UV-vis absorption spectra of (A) pure Zn 2 GeO 4 samples prepared from different solvents (Inset: plots of (αhv) 2 versus energy (hv) for the band gap energies of different Zn 2 GeO 4 ; (B) The UV-vis absorption spectra of g-C 3 N 4 and g-C 3 N 4 /Zn 2 GeO 4 (1:1) composites; (C) The UV-vis absorption spectra of g-C 3 N 4 /Zn 2 GeO 4 (0.5:1)-EG, g-C 3 N 4 /Zn 2 GeO 4 (1:1)-EG and g-C 3 N 4 /Zn 2 GeO 4 (2:1)-EG in compassion to g-C 3 the density of oxygen vacancies over the (110) surface is higher than that of the (001) surface, which are very important for the production of active •OH species as the H 2 O molecules dissociate in the oxygen vacancy.…”
Section: Photocatalytic Degradationmentioning
confidence: 69%
“…46 Figure 9A shows the photodegradation efficiencies of MB using g-C 3 N 4 /Zn 2 GeO 4 (1:1)-EG as photocatalyst under visible light irradiation by adding different scavengers, it can be observed that the photocatalytic degradation efficiency of MB decreased when the quencher of isopropyl alcohol and Lcarnosine were introduced, demonstrating the dominant role of •OH and •O 2 − species for MB degradation. To further clarify the active species dominated in the MB degradation process using g-C 3 N 4 /Zn 2 GeO 4 (1:1)-EG composite as photocatalysts, photocatalytic experiments of (0.1 mmol/L L-carnosine) and h + (6.0 mmol/L triethanolamine, TEOA) were applied to the photocatalytic system.…”
Section: Catalytic Mechanism and Stability Of Photocatalystmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Previous studies have proved that semiconductor photocatalyst exerts a crucial role in photocatalytic process. Recently, a number of semiconductors have been explored and tested to work as an efficient photocatalyst, such as TiO 2 , 15 Bi 2 WO 6 , 16 ZnO, 17 Zn 2 GeO 4 , 18 Cu 2 O, 19 etc. However, the applications of these traditional semiconductors in the field of photocatalysis have been greatly limited because they can only be activated under the irradiation of ultraviolet light.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40][41] Similarly, heterojunction photocatalysts have been studied due to its ability to prevent the electron-hole recombination. [42][43][44][45][46][47] V 2 O 5 was found to have improved photocatalytic activity due to the fact that the Al 2 O 3 particles trap photogenerated holes, hence enhancing the photocatalytic performances. 49 The addition of reduced graphene oxide (rGO) into V 2 O 5 has been shown to effectively separate the photogenerated charges due to the fact that the rGO serves as a trapping agent of the photogenerated electrons.…”
Section: Introductionmentioning
confidence: 99%